Library User Survey School La Salle - Aguilar, Damaris (1983)
There is emphasized the occupation of the school librarian in relation by the program of education of the Institution and there is analyzed the physical plant of the library, his bibliographical material and I equip in relation with the conditions that this one possesses to develop a good labor librarian in the College Go out For Her